Simbol Baal dalam Kisah Nabi Ilyas: Kajian Intertekstual Semiotik antara Al-Qur’an dan Al-Kitab: The Symbol of Ba'al in the Story of the Prophet Ilyas: An Intertextual Semiotic Study of the Qur'an and the Bible - Halci R, Qadhra Putri Rafla (Ulumul Qur'an: Jurnal Kajian Ilmu Al-Qur'an dan Tafsir, 2025)
This study aims to explore the symbolic and intertextual meaning of Baal in the story of Prophet Elijah/Ilyas in the Qur’an and the Bible. Utilizing Julia Kristeva’s intertextual theory and semiotic analysis, this qualitative research compares the theological and ideological narratives surrounding Baal in both scriptures. The study finds that Baal functions as a universal symbol of deviation from monotheism, presented dramatically in the Bible and concisely in the Qur’an. While the Bible narrates Baal as a mythological deity defeated in a dramatic confrontation, the Qur’an reinterprets Baal as a symbol of shirk, emphasizing ideological purity. The findings reveal not only structural narrative similarities but also reinterpretations that align with each religious framework. This research contributes to the understanding of prophetic continuity and religious symbolism in the Abrahamic traditions, offering new insights into scriptural dialogue through intertextuality.